1979
DOI: 10.1159/000194027
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Response to Carbon Dioxide after Propranolol in Normal Subjects

Abstract: The ventilatory response to carbon dioxide, using the rebreathing technique, was investigated in 5 healthy nonsmoker volunteers, without obstructive bronchopathy. The administration of propranolol (20 mg) in a single oral dose did not produce significant modifications of the slopes of the response curves, but caused a significant increase of the intercept of the curves (p < 0.05). Since no changes of the spirographic values were noted, the results obtained were attributed to a decrease of ventilation. It is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…after the administration of the four drugs showed that only propranolol increased the intercept of the curve of the ventilatory response, in comparison to the value ob tained after administration of placebo. The slope of this curve was not changed as previously observed [2], Mepindolol and salbutamol did not show modification of Ve in terms of slope and intercept during rebreathing test (table III).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…after the administration of the four drugs showed that only propranolol increased the intercept of the curve of the ventilatory response, in comparison to the value ob tained after administration of placebo. The slope of this curve was not changed as previously observed [2], Mepindolol and salbutamol did not show modification of Ve in terms of slope and intercept during rebreathing test (table III).…”
Section: Discussionsupporting
confidence: 83%
“…The results obtained by administration of propranolol gave con flicting results: in fact both a reduction of ventilatory response to CO? [2,7] and no modifications [8] have been reported.…”
Section: Introductionmentioning
confidence: 92%
“…There are controversies in the Patrick and Pearson [1978] found that pro pranolol had no effect on the C 0 2 response curve. Bosisio et al [1979] found a shift to the right of the ventilatory response to C 02 without change of slope after propranolol. Wc have found that metoprolol, proprano lol and exprenolol do not affect the ventila tory response to C 0 2 in healthy human sub jects [Folgering and Braakhekke, 1980], In another study where we infused beta-adre nergic drugs selectively into the vertebral artery of cats, we found an increased phren ic nerve activity after beta-mimetics and a decreased activity after beta-blockers [Fol gering, 1980], Scheen et al [1976] suggest that beta-adrenergic drugs only affect the ventilation in states of increased sympathoadrenergic activity such as exercise.…”
Section: Introductionmentioning
confidence: 81%
“…The measurement of ventilatory re sponse to carbon dioxide is well estab lished as a method of assessing the action of drugs on ventilatory drive [36], Pro pranolol and several other (3-adrenergic blocking drugs have been shown to have a significant influence on the CO; respon siveness [5,8,28,36], while other investi gators did not find any changes following beta-blockade [6,21,22,29,37], In all of these studies, the (modified) Read Method [31] was used and measurements were evaluated in terms of slope and intercept values [32], Unlike previous investigators, we mea sured both FIco; and PaCo; instead of PAco,. Thus, during room air breathing, the effects of bupranolol on ventilation must be interpreted with respect to PaCO; as the dependent variable.…”
Section: Discussionmentioning
confidence: 99%
“…With rebreathing techniques, however, controversial results have been reported concerning C 0 2 sensi tivity after propranolol [5,6,8,21,22,28,29,36,37] and several other (3-adrenergic blocking drugs [6,21,22,37]. From these results it is unclear whether (3-blockade af fects the ventilatory response or the C 0 2-dependent central drive.…”
Section: Introductionmentioning
confidence: 99%